Technical and Financial Feasibility of Information Technology Enabled Public Distribution System - Joshipura, Nehal Mayank; Joshipura, Mayank Harshvadan (Prabandhan: Indian Journal of Management, 2013)
This paper tries to address an issue of massive inefficiencies and leakages in one of the largest public distribution systems in the world. Diversion of public distribution system commodities is beyond imagination, and that leads to huge losses to the government and more importantly, the targeted beneficiaries of the public distribution system remain deprived of benefits. This study concludes that it is feasible - both on the technology and the financial front - to establish an effective public distribution system that helps plugging leakages and diversion of commodities and making sure that benefits reach the targeted population and that too, in a country with poor infrastructure, so much so that almost one-sixth of the villages in the country do not even have electricity. In addition, this study highlights how information technology can be leveraged to provide its benefits to the population at the bottom of the pyramid.